The Effect of In-Store Logistics Performance, Store Image, Sales Promotion, and Service Quality on Customer Satisfaction - Sari, Yulia Kartika; Gani, Ariel Nian; Zhafiraah, Nazma Riska (SAN Scientific, 2023)
The purpose of this study is to determine the effect of In-Store Logistics performance, Store Image, Sales Promotion, and Service Quality on Matahari Department Store Consumers. The population in this study is Matahari Department Store consumers in Mal Artha Gading. The sampling technique used is purposive sampling. The number of respondents in this study was 100 respondents. Data was collected by distributing questionnaires. The data analysis methods used are multiple regression analysis, t-test (partial), and F-test (simultaneous). The results of this study show that: (1) partially In-Store Logistics performance has a positive effect on customer satisfaction. (2) A partially stored image has a positive effect on consumer satisfaction. (3) partially sales promotion has a positive effect on customer satisfaction. (4) partial service quality has a positive effect on customer satisfaction. The value of adj R2 0.733 shows variations in the dependent variable. The managerial implications of the Influence of In-Store Logistics Performance, Store Image, Sales Promotion, and Service Quality on Customer Satisfaction at Matahari Department Store can include several key aspects, namely optimizing In-Store Logistics Performance by improving operational efficiency where management needs to ensure that in-store logistics operations run efficiently this can involve monitoring stock, in-store distribution.